2011
DOI: 10.1007/s12526-010-0071-y
|View full text |Cite
|
Sign up to set email alerts
|

Macrobenthos of the nearshore Aleutian Archipelago, with emphasis on invertebrates associated with Clathromorphum nereostratum (Rhodophyta, Corallinaceae)

Abstract: In the Aleutian Islands, Alaska, crustose coralline algae can be widespread in the low intertidal and shallow subtidal regions, and cover most available hard substrates. The longevity and slow growth-rate of coralline algae make them vulnerable to major disturbances, including anthropogenic disturbances and ocean acidification. Subtidal habitats dominated by crustose coralline algae are often associated with sea urchin-barren grounds and regarded as supporting limited invertebrate communities, especially compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 41 publications
(74 reference statements)
1
31
0
Order By: Relevance
“…The coralline provides a surface for algal epiphytes, and both the corallines and the epiphytes are grazed by many invertebrates. They are also very important producers of secondary biomass, mostly by providing a porous, reef-like habitat to innumerable invertebrates that utilize mostly planktonic sources of primary production (Chenelot et al, 2011). Additionally, they provide significant ecosystem support for Subarctic-Arctic fisheries that are now expanding in importance.…”
Section: S M I T H S O N I a N C O N T R I B U T I O N S T O T H E M mentioning
confidence: 99%
See 2 more Smart Citations
“…The coralline provides a surface for algal epiphytes, and both the corallines and the epiphytes are grazed by many invertebrates. They are also very important producers of secondary biomass, mostly by providing a porous, reef-like habitat to innumerable invertebrates that utilize mostly planktonic sources of primary production (Chenelot et al, 2011). Additionally, they provide significant ecosystem support for Subarctic-Arctic fisheries that are now expanding in importance.…”
Section: S M I T H S O N I a N C O N T R I B U T I O N S T O T H E M mentioning
confidence: 99%
“…In both the Atlantic and the Pacific, these carbonateencrusted bottoms have been widely referred to as "coralline, sea urchin barrens" (Mathieson et al, 1991;Estes and Duggins, 1995;Steneck et al, 2002); however, this description is certainly a misnomer, as they may well be among the richer shallow marine bottoms of the marine Holarctic (Himmelman, 1991;Chenelot et al, 2011). The Chenelot et al (2011) study focused on abundant invertebrates resident in Clathromorphum nereostratum in the Aleutian Islands, but it is likely that a similar relationship exists for cor-stromes in the northwestern North Atlantic.…”
Section: The Distribution Of Clathromorphum Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chenelot et al (2011) sampled at 50 sites (2006)(2007) from the Eastern to Western Aleutians Islands, Alaska, as part of the Alaska Monitoring and Assessment Program. Abundant, thick crustose coralline algae (Clathromorphum nereostratum) found at these sites provided microhabitats for 707 invertebrate taxa, many of which were cryptic within the 2-10 cm thick matrix of corallines.…”
Section: Benthic Studiesmentioning
confidence: 99%
“…Numerous invertebrates are dependent on seaweeds with varying morphological features, including the complex three-dimensional Macrocystis (Graham 2004), the compact spongy Codium (Trowbridge 1998;Bulleri et al 2006), the fan-like broad thallus of Chondrus (Janiak and Whitlatch 2012), the crustose coralline algae Clathromorphum (Chenelot et al 2011) and the calcareous rhodoliths (Foster 2001). Steller et al (2003) reported that the total number of organisms supported by the coralline red algal rhodoliths significantly increased with both complexity (branching density) and space available (thallus volume) when compared with adjacent sand community.…”
mentioning
confidence: 99%